Prevalence and risk factors for anxiety and depression among school going adolescent of Rajkot, Gujarat, India - Patel, Dipal; Patel, Dhara (International Journal of Contemporary Pediatrics, 2020)
Background: Adolescence is a period of turmoil, leading to several mental health challenges including anxiety and/or depression. Anxiety and depressive disorders affects 10-15% of adolescents. Anxiety and depression are associated with substantial negative effects on adolescent’s social, emotional and academic success. This leads to poor social and coping skills, low self-esteem, perceptions of social rejection, and difficulty forming friendships. This study was carried out with an objective to study prevalence and risk factors for anxiety and depression among adolescents. Methods: A cross sectional study conducted from April 2014 to December 2015 among 1026 school going adolescents from 4 schools of Rajkot, Gujarat, India. Anxiety and depression were measured using Beck Anxiety Inventory (BAI) and Beck Depression Inventory (BDI) respectively. Chi-square test was applied as test of significance. Results: Majority of the students (58.1%) was belonged to early adolescent age group. Two third were males. Maximum adolescents (42.5%) were coming from class III. Prevalence of moderate-severe anxiety and depression was 9.9% and 18.5%. Anxiety was not significantly associated with age, gender and socio economic class. Prevalence of depression was significantly higher in boys (20.5%) as compared to girls (14.5%, p=0.02). Moderate to severe depression was gradually increased with increasing in age. Adolescent from upper socio economic class (I, II, III- 19.1%) were severely depressed than adolescent from lower socio economic class (IV, V- 4.1%). Conclusions: Anxiety and depression was significantly present in adolescent age group. Depression was commonly observed in boys and gradually increased with increasing in age. There is need of strengthening school health services with screening and cost effective interventions to minimize the risk of drug abuse, suicide and violence.